2019
DOI: 10.3390/math7090774
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Prices and Agricultural Commodities: An Investigation of Their Relationship

Abstract: Brazil is an important player when it comes to biofuel and agricultural production. The knowledge of the price relationship between these markets has increasing importance. This paper adopts several tools, namely the Bai–Perron test of breakpoints, the Johansen cointegration test and the vector error correction model exploited by the orthogonal impulse response and the forecast error variance decomposition, for investigating the price transmission among the ethanol and the main Brazil’s agricultural commoditie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 72 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…Such goods revealed price transmission (cointegration) in a previous study [19]. In fact, not only some agricultural commodities [9,28], but also relevant commodities for Brazil's economy, (e.g., the cotton, live cattle, corn, soybean, Arabica coffee, and Robusta coffee) have a direct linkage with the Brazilian ethanol.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…Such goods revealed price transmission (cointegration) in a previous study [19]. In fact, not only some agricultural commodities [9,28], but also relevant commodities for Brazil's economy, (e.g., the cotton, live cattle, corn, soybean, Arabica coffee, and Robusta coffee) have a direct linkage with the Brazilian ethanol.…”
Section: Introductionmentioning
confidence: 71%
“…The presence of breakpoints in the ethanol price series was identified using the Bai-Perron algorithm [41], and the period and sub-periods were classified as follows; Full-period (Jan/2011 to Dec/2018), Sub-period 1 (P 1 : Jan/2011 to May/2012), Sub-period 2 (P 2 : May/2012 to Nov/2013), Sub-period 3 (P 3 : Nov/2013 to Sept/2015), Sub-period 4 (P 4 : Sept/2015 to Oct/2017) and Sub-period 5 (P 5 : Oct/2017 to Dec/2018). Table 1 summarizes the cointegrations found by David et al [19]. Table 1.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…It was concluded that oil price shock does not induce much of the fluctuations in the ASEAN-5 economies. Another study [8] examined the price of ethanol and commodities in Brazil using the Bai-Perron test, the Johansen test, and the vector error correction model. The results showed that there was a short-term relationship between ethanol and commodities.…”
Section: Introductionmentioning
confidence: 99%